(untitled) (Global Journal of Management and Business Research, 2025)
This study endeavors to examine the impact of electronic human resources management (E-HRM) systems on achieving a sustainable competitive advantage (SCA) in the health sector in Riyadh and Eastern region in Saudi Arabia by combine sustainable innovation (SI) and organization commitment (OC). The research was applied in health units that rely on E-HRM in their work, such as: electronic recruitment and online training. Structured questionnaires were used to collect data from respondents. Overall, 575 questionnaires were distributed and received 468, response rate 81.4%. The research data was analyzed using Amos-SEM. Research result: E-HRM have a positive and significant effect on SCA, SI, and OC, SI and OC they have a positive and significant effect on SCA. SI and OC are able to mediate the influence of E-HRM on SCA. The study adds to existing literature on who E-HRM impacts SI, OC and SCA. The current study has addressed gaps by empirically analyzing these relationships in the context of Kingdom of Saudi Arabia health sector. It integrates E-HRM, innovation, OC and competitive advantage within the context of sustainability in health sector.